SIFAT KIMIA TANAH PASCA KEBAKARAN LAHAN DI KEBUN KELAPA SAWIT DI KABUPATEN TULANG BAWANG PROVINSI LAMPUNG - Omar Nurcholis; Syahrul Kurniawan (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2021)
Fire is a serious problem that must be faced in the management of forest or plantation areas. Land fires have caused huge losses of soil nutrient. Lampung is one of the provinces in Indonesia having a problem related to land fires. The purpose of this study was to analyze the impact of land fires on the soil base cations (K, Mg, Ca, Na) and cation exchange capacity (CEC) in three different planting zones (i.e. fertilization, harvesting path, and frond stack areas) within oil palm plantations between land with low fire intensity and land with high fire intensity. Observations were made using a survey method in three zones of oil palm plantations, including fertilization area, harvesting path, and frond stack area. Soil samples were collected by using a soil drill at two depths, namely 0-10 cm and 10-30 cm from the soil surface. The study showed that at depth 0-10 cm, land A (land with low fire intensity) had higher K, Na, and Ca contents, as well as higher CEC as compared to land B (land with high fire intensity). At depth 10-30 cm, field A had higher K and CEC content, and lower Mg content than land B. comparing among different zones of oil palm plantations also showed that soil exchangeable K and Mg were significantly different, especially at depths of 10-30 cm. This was due to differences in land management (i.e. fertilization and liming).